2016
DOI: 10.1088/1361-648x/29/7/075902
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal growth, structure and magnetic properties of Pr2Hf2O7pyrochlore

Abstract: Abstract. Large single crystals of the pyrochlore Pr 2 Hf 2 O 7 have been successfully grown by the floating zone technique using an optical furnace equipped with high power Xenon arc lamps. Structural investigations have been carried out by both synchrotron X-ray and neutron powder diffraction to establish the crystallographic structure of the materials produced. The magnetic properties of the single crystals have been determined for magnetic fields applied along different crystallographic axes. The results r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Furthermore, magnetic measurements of Ce 1– x Zr x O 2 solid solutions annealed under air at high temperatures show diamagnetic signals and consequently the absence of Ce 3+ . Therefore, within our experimental measurement conditions ( T < 400 K), we can assume the only presence of a Pr 4+ /Pr 3+ mixture and 100% Ce 4+ so that all Curie constants can be calculated per mole of praseodymium only. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, magnetic measurements of Ce 1– x Zr x O 2 solid solutions annealed under air at high temperatures show diamagnetic signals and consequently the absence of Ce 3+ . Therefore, within our experimental measurement conditions ( T < 400 K), we can assume the only presence of a Pr 4+ /Pr 3+ mixture and 100% Ce 4+ so that all Curie constants can be calculated per mole of praseodymium only. …”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the theoretical effective moments of Pr 4+ and Pr 3+ ions (2.54 and 3.58 μ B , respectively, C Pr 4+ = 0.806 emu K/mol, C Pr 3+ = 1.602 emu K/mol), their proportion can be evaluated for all of the Ce 1– x – y Zr x Pr y O 2– z series (Table and Figure ). At low temperature ( T < 175 K), a slight deviation of the Curie–Weiss law must be mentioned, leading to consider the more general Van Vleck formula taking into account the various populations of fundamental and excited states and the spin–orbit coupling effect. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(26)(27)(28)(29)(30)(31) However, a single-crystal form is preferable for X-or γ-ray measurements owing to their high optical transparency, density, and homogeneity. Since the crystal growth of RE 2 Hf 2 O 7 is difficult owing to the high melting points (~2400 °C), there have only been a few reports on the crystal growth of pyrochlore RE 2 Hf 2 O 7 (e.g., Nd 2 Hf 2 O 7 (32) and Pr 2 Hf 2 O 7 (33) ). In our previous works, La 2 Hf 2 O 7 , Gd 2 Hf 2 O 7 , and Lu 2 Hf 2 O 7 single crystals were successfully synthesized using an optical floating zone furnace equipped with Xe lamps, and the scintillation properties of the single crystals were reported for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rare-earth hafnate, since crystal growth is quite difficult because of the high melting point (~2400 °C), few studies on the growth of pyrochlore rare-earth hafnate compounds have been reported. (16)(17)(18) Previously, we introduced the optical floating zone (FZ) method as an effective and powerful technique for searching new oxide scintillators with high melting points. (19)(20)(21)(22)(23) Up to now, pyrochlore RE 2 Hf 2 O 7 (RE = La, Gd, Lu) single crystals have been prepared using an optical FZ furnace equipped with Xe lamps, and the scintillation properties of these single crystals were reported for the first time by Nakauchi et al (18) To improve scintillation characteristics by increasing oxygen vacancies, Zr and Ti ions with radii smaller than that of the Hf ion are introduced into RE 2 Hf 2 O 7 single crystals to distort the crystal lattice because Hf-based oxide materials typically show luminescence due to oxygen vacancies such as F and F + centers.…”
Section: Introductionmentioning
confidence: 99%